2006
DOI: 10.1093/ejo/cjl004
|View full text |Cite
|
Sign up to set email alerts
|

A study model based photographic method for assessment of surgical treatment outcome in unilateral cleft lip and palate patients

Abstract: The aim of this study was to test the reliability of using digital photographs of study models as an alternative to the use of plaster study models in the assessment of surgical treatment outcome in 5-year-old children with unilateral cleft lip and palate (UCLP). Fifty-six dental study models available from the Managed Clinical Network for Cleft Services in Scotland (CLEFTSiS) database of patients aged 5-years with non-syndromic UCLP were employed. An experienced examiner scored the plaster study models using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…These results are in line with previous cleft care studies which have determined “Good” to “Very Good” levels Altman, 1991) of intra- and interobserver agreement for plaster models with photographs Nollet et al, 2005; Ali et al, 2006; Liao et al, 2009; McAuliffe et al, 2010) and plaster models with digital models (Asquith and McIntyre, 2012; Leenarts et al, 2012; Servet et al, 2012; Chawla et al, 2013) (Tables 1 and 2). Our investigation was novel by employing intraoral 3D scanning, as such models have not been investigated for the assessment of dental arch relationships in cleft care to date.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in line with previous cleft care studies which have determined “Good” to “Very Good” levels Altman, 1991) of intra- and interobserver agreement for plaster models with photographs Nollet et al, 2005; Ali et al, 2006; Liao et al, 2009; McAuliffe et al, 2010) and plaster models with digital models (Asquith and McIntyre, 2012; Leenarts et al, 2012; Servet et al, 2012; Chawla et al, 2013) (Tables 1 and 2). Our investigation was novel by employing intraoral 3D scanning, as such models have not been investigated for the assessment of dental arch relationships in cleft care to date.…”
Section: Discussionsupporting
confidence: 90%
“…A very few studies have been done using the mHB index. Among them, most of the studies (Ali et al, 2006; Wangsrimongkol and Jansawang, 2010; Manosudprasit et al, 2011; Dobbyn et al, 2012; Dobbyn et al, 2013) are about the reliability and validity of this index. It can be noted that Kappa value of mHB in this study also has been shown very good intra- and interexaminer agreements, as in previous studies (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the 5-year-olds’ index is applied to plaster models, but the potential challenges of physical models, such as the inconvenience of transportation and the risk of damage, have led to investigations into alternative mediums. The use of digital photographs of plaster models (Nollet et al, 2004; Ali et al, 2006) and intraoral clinical photographs (Liao et al, 2009; McAuliffe et al, 2011) have been shown to be reliable alternatives.…”
Section: Discussionmentioning
confidence: 99%